Integrating plant richness in forest patches can rescue overall biodiversity in human-modified landscapes - Farah, Fabiano Turini [UNESP]; Muylaert, Renata de Lara [UNESP]; Ribeiro, Milton Cezar [UNESP]; Ribeiro, John Wesley [UNESP]; Sa Abilio Mangueira, Julia Raquel de; Souza, Vinicius Castro; Rodrigues, Ricardo Ribeiro (Elsevier B.V., 2017)
The substitution of natural ecosystems with agriculture has led to the establishment of human-modified landscapes globally. In some tropical regions, this process is decades-old, allowing for the study of the effect of such modifications on the remaining biodiversity. However, unlike forest fragments inside regions with extensive primary coverage, the conservation value of ecosystems embedded within intensive farming, i.e., the anthropogenic matrices, has long been ignored, as have the effects of the landscape on such disturbed forest communities. Since the degradation process is predicted to cause the collapse of these fragmented forests, we can choose either to neglect them or to attempt the reversal of the degradation process for biodiversity conservation. Here we investigated the possible influence of landscape predictors on numerous plant species and on the relative proportions of different functional groups. Our results revealed that the richness found in human-modified landscapes had significantly more species than the protected reserves (+90%). The distribution of species suggested that any forest patch is likely to harbour a rare species. Generalised linear models and quantile regressions showed that forest cover and connected area influences the persistence of pioneer species and non-pioneer species of the canopy and zoochorics, with the latter also depending on slope. Rarefaction analysis revealed that natural remnants retain many species, even in sites with less than 20% forest cover. The presence of many zoo-choric and non-pioneer canopy species may indicate a qualitative aspect to support conservation-restora tion efforts. These results indicate that the current strategy, which is limited to the preservation of biodiversity in public conservation reserves, should be reconsidered and should include smaller remnants of the natural ecosystem in a regional context and adopt large-scale restoration strategies to preserve the species pool. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Forest fragmentation; Anthropogenic landscape; Forest coverage; Vegetal richness; Atlantic Forest; Seasonal forest